Cu 필라 솔더 범프의 리플로우 전후 형상변화 및 모델링 - 김상혁; Sang Hyuk Kim; 신한균; Han Kyun Shin; 박채민; Chae Min Park; 김동욱; Dong Uk Kim; 차필령; Pil Ryung Cha; 이의형; Ui Hyoung Lee; et al. (대한금속·재료학회지, 53(7), 2015)
A Cu pillar bump was fabricated by consecutive plating of Cu and Sn. Here, we investigated the change in shape of Sn, and the formation of intermetallic compound during the reflow process. At first, we made a cylindrical shape of Sn in various thickness and then, the Sn was changed into a truncated sphere (Sn bump) on a Cu pillar through the reflow process. When the Sn thickness was a third of the Cu pillar diameter, the reflowed bump radius had a minimum value and the bump-height change at that time had a maximum value. Such results were well understood based on the truncated sphere model.